2019
DOI: 10.1007/s13201-019-0978-9
|View full text |Cite
|
Sign up to set email alerts
|

The survey of application of the linear and nonlinear kinetic models for the adsorption of nickel(II) by modified multi-walled carbon nanotubes

Abstract: Pollution due to the presence of nickel is of great importance because of its toxic nature and non-biodegradability. Nickel is one of the most common heavy metals used in the industry. The purpose of the study is to investigate the efficiency of modified multi-walled carbon nanotubes (MWCNTs) on the adsorptive removal of nickel (II) from its aqueous environment and also to survey the applicability of the linear and nonlinear adsorption kinetic models on the process. The effects of process parameters including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Ahmadi et al reported that the optimal pH for Ni (II) ions adsorption on MWCNTs from aqueous solution is 10. ey mentioned that it could be attributed to the surface of the MWCNTs and is negatively charged. pH and the Ni (II) ions are positively charged; thus, electrostatic attraction is increased between them which enhanced the removal efficiency [38].…”
Section: Rsm Modelingmentioning
confidence: 99%
“…Ahmadi et al reported that the optimal pH for Ni (II) ions adsorption on MWCNTs from aqueous solution is 10. ey mentioned that it could be attributed to the surface of the MWCNTs and is negatively charged. pH and the Ni (II) ions are positively charged; thus, electrostatic attraction is increased between them which enhanced the removal efficiency [38].…”
Section: Rsm Modelingmentioning
confidence: 99%
“…The increased rate of removal efficiency at pH of 6 is related to the point of zero charge and pKa of the CuO-NPs and PG, respectively. The point of zero charge is defined as the pH at which the net charge of the total particle surface is equal to zero (25). The PG pKa was reported as 2.75, and the pHzpc of CuO-NPs was equal to 9.4.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…This can be attributed to the increase in adsorption sites with more nanoparticles resulting in a marked increase in adsorption capacity (33). The decrease in the adsorption capacity is also ascribed to active adsorption sites which are unsaturated during the process of PG removal on CuO-NPs (25,34).…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) are one novel nano-adsorbent used in water pollution treatment over the past decades (Alimohammady et al, 2017;Ahmadi et al, 2019). Compared to zeolite, kaolinite, chitosan, biopolymer, and other traditional adsorption materials (Zhang M. et al, 2019;Fu et al, 2021;Khan et al, 2021), CNTs have more excellent aspect ratio, specific surface area, and unique one-dimensional structure (Sone et al, 2008;Aliyu, 2019), and all these structural features provide convenient conditions for metal ions adhering.…”
Section: Introductionmentioning
confidence: 99%